Pencegahan dan Edukasi Dermatitis Kontak pada Petani Desa Mlati, Kabupaten Grobogan - Maria Estela Karolina; Adelia Hanung Puspaningtyas; Fania Rizky Ramadiani; Dyah Ayu Shinta Ratnasari; Che Guevara Islami; Nadhifa Rira Rizkika; Natania Daya Emerald; Nazrin Firda Nur Dzakia; Siti Nabilah Daniswara; Zamzami Ismail Bachtiar Silaen (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia, as an agricultural country, has a large population working in the agricultural sector. Agricultural activities often involve the use of chemicals that can cause skin disorders, one of which is contact dermatitis. Contact dermatitis is an occupational disease with a high prevalence, both globally and nationally. As a form of concern for the increasing number of dermatitis cases among farmers, a community service activity was conducted in Mlati Village, Grobogan Regency. This activity aimed to increase farmers' awareness and knowledge regarding contact dermatitis prevention. The intervention included educational sessions, interactive discussions, role-plays, pre- and post-tests, and the distribution of skin health information leaflets. The activity was carried out by the Health Promotion Team from the Faculty of Medicine, Semarang State University. The evaluation results showed an increase in participants' understanding of the symptoms of contact dermatitis by 11.86% of the 21 participants who attended. Materials considered important by participants included the importance of maintaining personal hygiene after contact with chemicals, as well as the use of personal protective equipment (PPE) during work. The participants' enthusiasm was also evident in their active participation in the discussion sessions and hands-on practice. However, there was still a lack of in-depth understanding of skin health care. This demonstrates the need for regular follow-up education to reinforce the program's positive impact. Overall, these activities demonstrate the critical importance of community-based health promotion in reducing the risk of occupational skin diseases and encouraging healthier and safer behavior changes in farmers.